A preliminary storage study on tomato-mango blend jam - Maypa, Niña P. (2001.)
Three experimental formulations of tomato-mango blend jam were subjected to a preliminary storage study for three months at room conditions.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tomato-mango jam